Elastic-Plastic Fracture Mechanics of Ductile Cast Iron Pipes - Jasim, Haider Hadi (Basrah Journal for Engineering Sciences, 2007)
In this paper, depends on the finite element method, the J-Integral program is developed for a stationary circumferential crack problem in elastic plastic fracture mechanics in pipes under static loading and pure bending moment condition. The program developed is applied to ductile cast iron pipes (DCIP) to analys the integrity assessment, i.e., the significance of crack growth by drawing both failure assessment diagram (FAD) and crack driving force diagram (CDF). A numerical procedure is used for elastic-plastic analysis depending on special equation to predict J-values taking account of the crack geometry and load condition. It is cleared that the results obtained from failure assessment diagram and crack driving force diagram are identical and J-integral method can be used to the onset of crack growth in (DCIP) under bending moment conditions.